2000
DOI: 10.1097/00006123-200009000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Adult Medulloblastoma: Prognostic Factors and Patterns of Relapse

Abstract: Late relapse is common among adult patients with medulloblastomas, and long-term follow-up monitoring is important. Because of the high risk of systemic failure among the low-risk patients treated with radiotherapy alone, the role of chemotherapy for this group of patients needs to be further investigated. Complete resection, the absence of brainstem invasion, and an overall radiotherapy duration of less than 48 days are important prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
92
3
21

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(128 citation statements)
references
References 35 publications
9
92
3
21
Order By: Relevance
“…It was stated that 29% of the recurrences occurred 5 years after treatment. [25] In our study, recurrence was detected in 3 patients at 39 th , 47 th , and 57 th months, found at the primary tumor location. Those patients died at 2 nd and 26 th months after recurrence.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…It was stated that 29% of the recurrences occurred 5 years after treatment. [25] In our study, recurrence was detected in 3 patients at 39 th , 47 th , and 57 th months, found at the primary tumor location. Those patients died at 2 nd and 26 th months after recurrence.…”
Section: Discussionsupporting
confidence: 46%
“…There was no recurrence or distant metastasis in the follow-up after adjuvant RT or CT. Recurrences develop mostly in posterior fossa. [23][24][25] A review of recurrence patterns indicated that recurrences occur mostly within 2 years in pediatric group. [26,27] This duration is longer for adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, adult medulloblastoma is arguably a biologically distinct challenge in that it exhibits a higher proportion of desmoplastic histological characteristics, shows more proclivity toward cerebellar hemispheric origin, possesses different proliferative and apoptotic indices, and demonstrates a notorious tendency for late relapse. 1,13 Metastatic disease spread via the cerebrospinal fluid is commonly present when this malignant embryonal tumor or the histologically related supratentorial PNET is diagnosed. 5 Thus, medulloblastoma demands a broader armamentarium than that provided by open resection.…”
mentioning
confidence: 99%
“…MBs are overwhelmingly found in pediatric patients, but can rarely occur within adult brain, where the tumor characteristics become very atypical. Adult MB is arguably a biologically distinct challenge in that it exhibits a higher proportion of desmoplastic histological characteristics, shows more proclivity toward cerebellar hemispheric origin, possesses different proliferative and apoptotic indices, and demonstrates a notorious tendency for late relapse with respect to the pediatric variants (Chan et al, 2000;Sarkar et al, 2002). MBs are thought to arise within the cerebellum, with approximately 25% originating from granule neuron precursor cells (GNPCs) (Gibson et al, 2010) after aberrant activation of the Sonic Hedgehog (Shh) pathway ( Figure 1B).…”
mentioning
confidence: 99%